Empowering unemployed people to process corn cob waste into briquettes as an alternative fuel in Ciherang village - Irwan, Yusril; Hidayat, Fery; Firmansyah, Eka Taufik (Institut Teknologi Nasional, Bandung, 2024)
When the corn harvest season arrives, the problem in Ciherang village is that corn cob waste that becomes rubbish. The solution is these corn cobs will be made into briquettes as an alternative fuel to replace LPG gas. Unemployed youth are trained to make corn cob briquettes, starting from the theory of making them to using briquette making tools. Then field practice of the pyrolysis process, crushing charcoal, sieving, mixing, pressing, and drying the briquettes. The instructors of this activity are students taking the course MSB 398 Applications of Mechanical Engineering to Society. From the results of the training, the young people who have been appointed by the village head can make corn cob briquettes correctly and can also provide input that supports the process of making these briquettes better and produce larger quantities in a faster time.